Study on Flow Field Optimization for SCR System of Coal-fired Power Plants. (August 2019) - Liu, Xiuru; Sun, Yiqing; Xue, Fangming; Su, Jingcheng; Chen, Feng
Abstract: Coal-fired power plants are undergoing ultra-low emission retrofits. When the flue structure of the SCR denitrification system of the existing unit is fixed, the internal baffles and static mixers need to be optimized to ensure the flow field uniformity, thus ensuring the denitrification efficiency and controlling the ammonia escape rate. For a 660 MW SCR system, numerical simulation of flue gas flow uniformity and cold state test of physical model were carried out. The results show that the uniformity of the flow field distribution and the mixing effect of ammonia and gas in the SCR denitrification system are effectively improved by adding deflectors and optimizing the static mixers. The research in this paper provides reference for similar engineering design and construction in the future.